ANALYSIS OF FIXED ASSETS OF THE ENTERPRISE: PROBLEMATICALLY-PROGNOSTIC APPROACH (INNOVATIVE ECONOMY, 2020)
Yakymova L.P., Smolnikova K.А. ANALYSIS OF FIXED ASSETS OF THE ENTERPRISE: PROBLEMATICALLY-PROGNOSTIC APPROACHPurpose. The aim of the article is substantiation of the content and algorithm of the problematically-prognostic approach to the analysis of fixed assets and its approbation at the enterprises which according to NACE-2010 are included into the section G (wholesale and retail trade, repair of motor vehicles and motorcycles).Methodology of research. General scientific and special methods of cognition in the research are used in the article, such as: methods of theoretical generalization and comparative analysis – for the analysis of relevant scientific literature; systematical approach, methods of analysis and synthesis – for the substantiation of the methods of analysis of fixed assets; ratio analysis – for the analysis of the efficiency of using fixed assets; methods of mathematical statistics – for assessing the risks associated with fixed assets; methods of econometrical analysis – for building models and assessing of the impact of indicators of fixed assets on the financial results of enterprises.Findings. The main contribution of the research consists in the inclusion of such stages in the traditional method of analysis of fixed assets, such as, integral assessment of the efficiency of use, analysis of risk and problematically (econometric) analysis of fixed assets, is substantiated. Empirical results confirm an increase of the information value of such analysis that contributes to the adoption of reasonable and timely management decisions.Originality. A method of analysis of fixed assets is proposed in the research, which includes the definition of the stages of analysis, the formation of a system of indicators, methods and information base for each stage of analysis, and, unlike the existing ones, has a problematically-prognostic focus, which makes it possible to perform a comprehensive analysis of fixed assets, to determine the directions of increasing the efficiency of their use, to assess the impact on the financial results of the enterprise.Practical value. The proposed method of analysis can be used by managers and investors for a deeper understanding of the problems associated with fixed assets of the enterprise. The empirical results of the research are recommended to be used as benchmark indicators in the analysis and development of a policy for the management of fixed assets at the enterprises of section G according to NACE-2010.Key words: fixed assets, ratio analysis, analysis of risks, econometric analysis, enterprises of section G according to NACE-2010.
Keywords: Key words; fixed assets; ratio analysis; analysis of risks; econometric analysis; enterprises of section G according to NACE-2010.